The impact of new information upon UK financial futures markets. - Anna Elizabeth Radcliffe (2003)
There is little published evidence on the reactions of UK financial futures prices and associated trading activity to new information. This thesis addresses this deficiency in the literature by focusing on two forms of information exposure in UK futures markets. These occur in the form of either a repo rate announcement or from information inferred from observing the historical pattern of transactions. This study examines the impact of the unexpected component of repo rate announcements on futures markets. We find that the size of the price reaction and the amount of associated trading activity following an announcement was generally explained by the degree of surprise. This study also examines the information content of trade arrival times, or trade durations in market microstructure. In particular we generalise Hasbrouck's VAR model, to determine the role played by trade durations in the price formation process and the autocorrelations of trades. We find that a buy transaction arriving after a long time interval has a lower price impact than a buy transaction arriving right after a previous trade. In addition, we model these trade durations using an autoregressive conditional duration (ACD) model. Although we find both the exponential and the Weibull distributions only partially account for the intertemporal correlations present in our duration data, we reject the exponential in favour of the Weibull. We also introduce a new asymmetric log-ACD model, where the next expected duration depends on the trade sign process.